2019
DOI: 10.1088/1741-2552/ab2610
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance 4 nV (√Hz)−1 analog front-end architecture for artefact suppression in local field potential recordings during deep brain stimulation

Abstract: Objective Recording of local field potentials (LFPs) during deep brain stimulation (DBS) is necessary to investigate the instantaneous brain response to stimulation, minimize time delays for closed-loop neurostimulation and maximise the available neural data. To our knowledge, existing recording systems lack the ability to provide artefact-free high-frequency (>100 Hz) LFP recordings during DBS in real time primarily because of the contamination of the neural signals of interest by the stimulation artefacts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…The input dynamic range is defined here as the width of amplitudes within which the THD remained lower than 1%. [ 26 ] The input dynamic range was determined for each characterized amplifier using physical measurements and simulations. The gain was calculated by dividing the amplitude of the output voltage from the THD data by the amplitude of the input signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The input dynamic range is defined here as the width of amplitudes within which the THD remained lower than 1%. [ 26 ] The input dynamic range was determined for each characterized amplifier using physical measurements and simulations. The gain was calculated by dividing the amplitude of the output voltage from the THD data by the amplitude of the input signal.…”
Section: Resultsmentioning
confidence: 99%
“…In hospital wards with multi‐frequency noise sources and in applications where concurrent neural sensing and electrical stimulation is required, for example in deep brain stimulation and spinal cord stimulation setups, the nonlinearity of the amplifying system must be minimized to avoid artifact coupling with the electrophysiological measurements through intermodulation. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although external systems were able to solve the artifact rejection problem ( Rossi et al, 2007 ; Arlotti et al, 2016b ; Petkos et al, 2019 ), the size and power constrains of implantable operations make the rejection of stimulation artifact a technical implementation challenge. The stimulation artifact consists of direct components (stimulus time-locked voltage transients) and indirect components (voltage decay in the inter-pulse period) ( Zhou et al, 2019 ).…”
Section: State Of the Art And Innovative Requirementsmentioning
confidence: 99%
“…Several filtering techniques have been proposed for removing artifacts from LFP recordings in the literature. These include a low-pass filter [4], a notch filter [5], and band-pass filters [6]. Specifically, [4] focused on removing high-frequency artifacts generated by DBS (130 Hz) by implementing a low-pass filter with a corner frequency of 50 Hz using Butterworth coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, [4] focused on removing high-frequency artifacts generated by DBS (130 Hz) by implementing a low-pass filter with a corner frequency of 50 Hz using Butterworth coefficients. Another study [5] reported that no biomarkers for Parkinson's disease were found in the frequency band between 125 and 155 Hz and thus a high-order (8th) Chebyshev notch filter with a center frequency of 140 Hz and stopband between 125 and 155 Hz was used to suppress artifacts during DBS. A band-pass filter with a frequency band between 100 Hz and the Nyquist frequency of 211 Hz was used to eliminate all stimulation interference [6].…”
Section: Introductionmentioning
confidence: 99%